Impact of AZFc deletion subtypes on sperm retrieval rates via micro-TESE and ICSI outcomes in non-obstructive azoospermia patients - Yanqing Xia; Ke Feng; Xiaowei Qu; Feng Wan; Cuilian Zhang; Haibin Guo (Scientific Reports)
Abstract This study aims to compare the sperm retrieval rate (SRR) achieved through microdissection testicular sperm extraction (micro-TESE) with the outcomes of intracytoplasmic sperm injection (ICSI) in patients with non-obstructive azoospermia (NOA) who exhibit a partial deletion of the azoospermia factor c(AZFc) region on the Y chromosome. From December 2016 to September 2023, the clinical data of patients with NOA who had AZFc deletions, which were identified through high-throughput sequencing, and who underwent micro-TESE were retrospectively analyzed. Based on the results of screening the AZFc region, the patients were categorized into three groups—the gr/gr deletion group (n = 17), the b2/b4 deletion group (n = 62), and the b2/b3 deletion group (n = 11). The SRR, embryo development, and embryo transfer outcomes were compared between the three groups. The SRR in the gr/gr deletion group was significantly lower than that in the b2/b4 deletion group (P = 0.010). Conversely, the SRR in the b2/b4 deletion group and b2/b3 deletion group were relatively high, at 64.5% (40/62) and 54.5(6/11),respectively; however, the number of micro-TESE procedures that extracted sperm with severe morphological abnormalities was 13, resulting in an available sperm rate of only 43.5% (27/62). No significant differences were observed across all groups regarding fertilized oocyte (2PN) rate, 2PN cleavage rate, D3 available embryo rate, high-quality embryo rate, blastocyst formation rate, number of transferred embryos, miscarriage rate, clinical pregnancy rate, or live birth delivery rate (P > 0.05). The micro-TESE outcomes in NOA patients with partial deletions in the AZFc region of the Y chromosome are most significantly negatively impacted by gr/gr deletion.Patients with b2/b4 deletion and b2/b3 deletion type should actively undergo surgical treatment to obtain biological descendants.